2021
DOI: 10.5194/os-17-221-2021
|View full text |Cite
|
Sign up to set email alerts
|

Properties of surface water masses in the Laptev and the East Siberian seas in summer 2018 from in situ and satellite data

Abstract: Abstract. Variability of surface water masses of the Laptev and the East Siberian seas in August–September 2018 is studied using in situ and satellite data. In situ data were collected during the ARKTIKA-2018 expedition and then complemented with satellite-derived sea surface temperature (SST), salinity (SSS), sea surface height, wind speed, and sea ice concentration. The estimation of SSS fields is challenging in high-latitude regions, and the precision of soil moisture and ocean salinity (SMOS) SSS retrieval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Despite certain progress in deriving sea surface salinity from satellite measurements in the Arctic Ocean, these products demonstrate proper accuracy only for high salinity values (>28-30), while there is no evidence that they operate well at salinities <25, which are typical for FSL (Matsuoka et al, 2016;Olmedo et al, 2018;Tang et al, 2018;Supply et al, 2020). In particular, satellite-derived sea surface salinity at the study area analyzed recently by Tarasenko et al (2021) was not properly validated against in situ salinity data for low-saline shelf areas. As a result, the presented satellitederived salinity distributions did not reproduce sharp salinity gradients typical for the outer border of FSL.…”
Section: Introductionmentioning
confidence: 90%
“…Despite certain progress in deriving sea surface salinity from satellite measurements in the Arctic Ocean, these products demonstrate proper accuracy only for high salinity values (>28-30), while there is no evidence that they operate well at salinities <25, which are typical for FSL (Matsuoka et al, 2016;Olmedo et al, 2018;Tang et al, 2018;Supply et al, 2020). In particular, satellite-derived sea surface salinity at the study area analyzed recently by Tarasenko et al (2021) was not properly validated against in situ salinity data for low-saline shelf areas. As a result, the presented satellitederived salinity distributions did not reproduce sharp salinity gradients typical for the outer border of FSL.…”
Section: Introductionmentioning
confidence: 90%
“…Despite seasonal changes in the plume structure, strong wind forcing also could substantially affect sea level and break the ADT-salinity correlation on a synoptic time scale. Strong and durable winds induce wind surges at the coastal areas, which is the case of the Kara Sea [32,[52][53][54]. The threshold value of wind speed, which causes change of sea level by more than 10 cm in the study area (i.e., comparable with plume-sea ADT difference) is equal to 6-8 m/s [32,55].…”
Section: Wind Forcing and Adtmentioning
confidence: 89%
“…However, further we analyze the causes of this feature and describe conditions, when ADT is indicative of satellite salinity and could be used for detection of the Ob-Yenisei plume. Surface salinity and ADT have certain negative correlation, namely, ADT at low salinities (0-20) is equal to 0-25 cm, which is greater than ADT at high salinities (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) equal to −20-20 cm. However, the observed variability of ADT within individual salinity values is very large.…”
Section: Surface Salinity Structure and Adtmentioning
confidence: 98%
See 1 more Smart Citation
“…Local ice melt water should have a low CDM signature; therefore, this would allow us to distinguish between sea ice melt water and river water, as detailed in [73] where they used SSS and Ocean Color data to discriminate between water masses. However, the analysis of isotope characteristics of freshened surface layers in the Kara Sea has revealed that its volume is composed of river water directly mixed with saline water [40,[74][75][76]. During late summer and autumn, the large river discharge determines the freshwater balance, while the contribution of sea ice melt is negligible [48].…”
Section: Correlation Between Sea Surface Salinity and Colored Detrital Mattermentioning
confidence: 99%